DESKRIPSI SISTEM DAN PROSEDUR AKUNTANSI PADA PERUSAHAAN DAERAH PT.SARANA PEMBANGUNAN MUARA ENIM - Aspahani Aspahani; Ermadiani Ermadiani (AKUNTABILITAS, 2012)
This study aims to create a common perception for the managers (management boardand all the technical aspects of financial management), a common perception for the accountingfunction in preparing the financial statements required both the internal and external parties, auniformity treatment and handling the incoming cash management aspects of both documentspolicy that is applied to the following reporting, a uniformity of treatment and management aspectsof the management of cash out either document or policy adopted and the following reporting, auniformity of treatment and management of non-cash aspects of good document management andpolicy applied as well as the following reports. addition, with the financial management manualwill provide guidance for the management of the performance of the functions of the financialmanagement and accountability.The study is conducted at the regional company, Sarana Pembangunan Muara Enim(SPME), In Muara Enim. This research uses normative yuridis method, through thesarafsinkronisation research applicable law. The data that had been collected was processed andanalyzed using descriptive qualitative method, ie the data collected will be settled based on itsquality, started with the analysis of the provisions in the regulations articles for the area offinancial accounting issues related to the author discussed. The provisions are then connected tothe next.The results of the study found that: planning and financial control mechanisms atregional company PT. Sarana Pembangunan Muara Enim (SPME) is regulated by variousgovernment regulations and regulatory uniformity of treatment as well as maintenance of financialmanagement in order to be done effectively and efficiently.The financial management in regionalcompany started from the preparation of the budget aspects of budget execution and accountabilityof the budget. The optimal performance in regional company will be achieved when the financialmanagement system has been carried out effectively and efficiently. The preparation of the systemsand codefication procedures of the transaction in PT. SPME is very important by using anacceptable commonly and reliable methodology, and refers to The Loss of National Accounts.